Avaliação da capacidade imunogênica de células leveduriformes de Sporothrix schenckii inativadas em modelo murino - Antunes, Tatiana de Ávila (2010)
Sporotrichosis is a subcutaneous mycosis of zoonotic character, cosmopolitan development subacute or chronic whose agent the dimorphic fungus Sporothrix schenckii affecting man and various species of animals, especially the domestic cat, being considered of interest to Public Healt. Considering the difficulties in the therapeutic treatment of ringworm in this animal species, including toxicity and the development of resistance to antifungal agents traditionally used to treat disease the study aimed evaluate the immunogenic capacity of yeast cells of S. schenckii inactivated both in immunoprophylaxis and immunotherapy of sporotrichosis. We used 160 Wistar albin rats (Rattus norvegicus) at 70 days (80 in immunoprophylaxis and 80 in immunotheraphy) were divided into four groups that were immunized three times every 15 days. The groups were divided as follows: G1 (control, mineral oil), G2 (Ag + incomplete freund adjuvant), G3 (Ag + Freund's complete adjuvant) and G4 (Ag + incomplete freund adjuvant + propolis). Preparation of the vaccine used was an isolate of S. schenckii from yeast in the form of a case of cutaneous sporotrichosis of domestic cat. The fungus was grown in medium liquid (Brain-Heart broth), incubated for 10 days at 370C and kept under constant agitation to obtain the yeast form. The culture was filtered through a double layer of sterile gauze, centrifuged, washed twice with buffered saline (PBS), homogenized and standardized in 108 cells of S. schenckii / ml. The cells were inactivated with 0.02% thimerosal and then emulsified with mineral oil, and vaccines packaged in sterilized sealed and kept at a temperature of 40C throughout the experimental period. Was used a dose of 0.1 ml/animal intramuscularly. Rats that received the vaccine as immunoprophylaxis after the three doses were challenged, and inoculated subcutaneously with 2X103 cells / ml of S. schenckii in the right footpad and evaluated for 10 days. Animals treated with immunotherapy were inoculated with the agent after 14 days and received three doses of immunogen. After the experimental period all were euthanized and necropsy to mycological examination, histopathology and counting colony forming units. The results were: immunoprophylaxis in the pathological changes showed statistically significant differences (P <0.05) in the vaccinated groups (G2, G3 and G4) compared to the control group (G1) to the point of inoculation, with no statistical difference the evaluation of internal organs. Immunotherapy clinical evaluation at the injection showed that there was no statistical difference among the four experimental groups, but at the end of the experiment the groups G1, G2, G3 and G4 had respectively 8.3%, 58.3%, 41.7 % and 50% of injuries in the process of regression and healing. In relation to injuries in other body areas only in the last week of the experiment, the G2 and G3 differ statistically (P <0.05) in the control group (G1). Pathological changes were found in the internal organs of the four experimental groups, but with a greater number of lesions in group CONT. Both in immunoprophylaxis and immunotherapy the retroisolation of the agent and count of colony forming units showed that there was growth of S. schenckii in the four experimental groups, but with less frequency and quantification of CFU at the point of inoculation and internal organs of the groups G2, G3 and G4. In histopathologic evaluation to determine the presence of granulomas and pyogranulomas focal and multifocal in the point of inoculation and internal organs of the four groups, but the animals that received immunoprophylactic changes were more restricted to the point of inoculation. The results indicate that the three vaccine formulations (AIF ACF and AIFP) used as immunoprophylactic and immunotherapy have not been effective for the remission of the lesions of experimental cutaneous sporotrichosis.